Carbide slag pretreatment enhances volatile fatty acid production in anaerobic fermentation of four grass biomasses. (1st November 2019) - Tao, Xue; Zhang, Panyue; Zhang, Guangming; Nabi, Mohammad; Wang, Siqi; Ye, Junpei; Bao, Shuai; Zhang, Qian; Chen, Na
Graphical abstract: Highlights: Carbide slag was first used to pretreat four grass biomasses to enhance VFA yield. Carbide slag disrupted the grasses structure and improved reducing sugar yield. The highest VFA yield of 8803.87 mg/L was achieved from treated turfgrass pruning. Carbide slag pretreatment enhanced fermentation VS removal and VFAs/SCOD ratio. Richness of phylum Firmicutes and genus Clostridium contributed to the high VFA. Abstract: Anaerobic fermentation of biomasses for volatile fatty acid (VFA) production has attracted widespread attention. Grass biomasses have the advantages of high yield, rapid and perennial growth, low lignin content and low input, etc. In order to improve VFA production from grass biomasses, carbide slag was applied to pretreat four grass biomasses ( panicum virgatum, triarrhena lutarioriparia, medicago sativa and turfgrass pruning) before anaerobic fermentation. Results showed that carbide slag pretreatment changed the structure of grass biomasses and enhanced their crystallinity index (CrI). The reducing sugar yield and VFA production from four pretreated grass biomasses were significantly improved. Pretreated turfgrass pruning was the most promising grass compared with other grass biomasses, with the highest VFA production of 8803.87 mg/L and volatile solid removal of 56.76%. Kinetic results indicated that the first order kinetic model, cone model and modified Gompertz model all fitted well with VFA production (R 2  > 0.96), and pretreated turfgrass pruning achieved the highest VFA production potential of 11270 mg/L. Turfgrass pruning was the most suitable grass biomass for enzymatic hydrolysis and anaerobic fermentation due to a lower lignin content and CrI. High VS removal revealed that carbide slag pretreatment promoted substrate hydrolysis and further VFA production. There existed a positive correlation between enzymatic hydrolysis and anaerobic fermentation of grass biomasses (R 2  = 0.9064). Results of microbial community structure indicated that the high VFA production from turfgrass pruning after carbide slag pretreatment was mainly contributed to enrichment of phylum Firmicutes and genus Clostridium .